2000
DOI: 10.1021/bi002292m
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Insulin Receptor's Kinase Domain Changes the Rate-Determining Step of Substrate Phosphorylation

Abstract: The insulin receptor and many other protein kinases are activated by relief of intrasteric inhibition that is regulated by reversible phosphorylation. The changes accompanying activation of the insulin receptor's kinase domain were analyzed using steady-state kinetics, viscometric analysis, and equilibrium binding measurements. Peptide phosphorylation catalyzed by the unphosphorylated basal-state kinase is limited by a slow rate of the chemical step, and the activated enzyme is limited by product release rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
61
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 51 publications
8
61
1
Order By: Relevance
“…Interestingly, in the presence of ATP, we found that WT-RET and 2B-RET had similar melting temperatures ( Table 1), indicating that the conformations of ATP-bound (active) WT-RET and 2B-RET enzymes were more similar than those of their autoinhibited forms. The lower melting temperature of the active forms was consistent with the thermodynamic effects of the release of autoinhibition in other kinases (24,25). Together, these data suggested that, in addition to altered kinase activity, changes in intramolecular interactions and a potential reduction in conformational rigidity might play significant roles in the functional effects of the M918T mutation in 2B-RET.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Interestingly, in the presence of ATP, we found that WT-RET and 2B-RET had similar melting temperatures ( Table 1), indicating that the conformations of ATP-bound (active) WT-RET and 2B-RET enzymes were more similar than those of their autoinhibited forms. The lower melting temperature of the active forms was consistent with the thermodynamic effects of the release of autoinhibition in other kinases (24,25). Together, these data suggested that, in addition to altered kinase activity, changes in intramolecular interactions and a potential reduction in conformational rigidity might play significant roles in the functional effects of the M918T mutation in 2B-RET.…”
Section: Resultssupporting
confidence: 70%
“…In the absence of ATP, we found that WT-RET was more conformationally stable or rigid than 2B-RET, as indicated by a higher melting temperature [midpoint of denaturation transition (T m ), 65.10jC; Table 1]. The relatively higher energy requirement for denaturation is consistent with the tightly folded, more stable conformation of an autoinhibited (inactive) kinase structure (24,25). 2B-RET had a lower melting temperature (T m , 62.65jC), suggesting a relatively more flexible protein conformation with a less rigid overall structure.…”
Section: Resultsmentioning
confidence: 62%
“…Enzymatic activation by ligand may represent an increase in k cat as has been shown for the EGFR (24,25) or in concomitant increases in k cat and decreases in K m as has been demonstrated for the IRK (40). In our study, we have made the novel finding that ligand can also regulate the specificity of a receptor kinase toward physiologically relevant substrates.…”
Section: Discussionmentioning
confidence: 53%
“…Many RTKs require phosphorylation of one or more conserved tyrosine in the activation loop for full catalytic activity (43). For example, IRK activation loop phosphorylation results in 25-and 40-fold decreases in K m values for ATP and peptide, respectively, and a 7-fold increase in k cat (40). Unlike IRK and other RTKs, the crystal structure of the EGFR catalytic domain revealed that the unphosphorylated A-loop exists in an open extended conformation consistent with an enzymatically active kinase (16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, kinetic evidence showed that ATP binding predisposes the unphosphorylated receptor for trans autophosphorylation (32). Given the appar-ent affinity of the kinase domain for MgATP of ϳ1 mM (1,7,18) and the intracellular ATP concentration of ϳ1 mM (possibly as high as 8 mM [37]), a significant fraction of the receptor's kinase domains should have nucleotide bound under physiological conditions and therefore should be nonlatent as an enzyme and nonlatent as a substrate (18). This raises the issue of whether latency is required to maintain the basal state and, conversely, whether the IR with nonlatent kinase domains can be kept from autophosphorylation and signaling.…”
mentioning
confidence: 99%